Are regions of the lumbar multifidus differentially activated during walking at varied speed and inclination?. (October 2016) - Crawford, Rebecca J.; Gizzi, Leonardo; Mhuiris, Áine Ni; Falla, Deborah
Abstract: Purpose: Lumbar multifidus is a complex muscle with multi-fascicular morphology shown to be differentially controlled in healthy individuals during sagittal-plane motion. The normal behaviour of multifidus muscle regions during walking has only received modest attention in the literature. This study aimed to determine activation patterns for deep and superficial multifidus in young adults during walking at different speeds and inclination. Methods: This observational cohort study evaluated ten healthy volunteers in their twenties (three women, seven men) as they walked on a treadmill in eight conditions; at 2 km/h and 4 km/h, each at 0, 1, 5, and 10% inclination. Intramuscular EMG was recorded from the deep and superficial multifidus unilaterally at L5. Activity was characterized by: amplitude of the peak of activation, position of peak within the gait cycle (0–100%), and duration relative to the full gait cycle. Results: Across all conditions superficial multifidus showed higher normalised EMG amplitude (p < 0.01); superficial multifidus peak amplitude was 232 ± 115% higher when walking at 4 km/h/10%, versus only 172 ± 77% higher for deeper region (p < 0.01). The percentage of the gait cycle where peak EMG amplitude was detected did not differ between regions (49 ± 13%). Deep multifidus duration of activation was longer when walking at the faster vs slower speed at all inclinations (p < 0.01), which was not evident for superficial multifidus (p < 0.05). Thus, a significantly longer activation of deep multifidus was observed compared to superficial multifidus when walking at 4 km/h (p < 0.05). Conclusions: Differential activation within lumbar multifidus was shown in young adults during walking. The prolonged, more tonic activation of deep relative to superficial regions of multifidus during gait supports a postural function of deeper fibres.